Developing Sports Tourism Attractions through Football Clubs: A Comparative Study of Indonesia, Thailand, and Ecuador - Angga Putra Wardana; Benjawan Yotrawat; Jonathan Quiroz (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the Study: This study aims to analyze the development of sport tourism through football clubs using a comparative study of Indonesia, Thailand, and Ecuador. The study focuses on examining the role of football clubs as tourism attractions, identifying internal and external influencing factors, and comparing sport tourism management strategies in the three countries. Methodology: This study employed a qualitative descriptive approach with a comparative research design. Data were collected through literature review, documentary analysis, and previous research studies on football-based sport tourism in Indonesia, Thailand, and Ecuador. Data analysis used an interactive analysis model consisting of data reduction, data display, and conclusion drawing, combined with SWOT analysis. Main Findings: The findings reveal that Indonesia’s strength lies in strong supporter loyalty and match atmosphere, although managerial and financial issues remain challenges. Thailand demonstrates more professional sport tourism management through government support and tourism integration. Ecuador shows strong cultural identity and football enthusiasm but faces infrastructure and promotional limitations. All three countries utilize football as a driver of local economic growth and tourism attraction. Novelty/Originality of this Study: This study introduces a cross-national comparative framework for examining football clubs as sport tourism attractions in emerging countries. It advances existing knowledge by integrating cultural, managerial, economic, and institutional perspectives to explain differences in football-based tourism development. The findings provide new insights into how contextual factors shape sustainable sport tourism strategies.